K-shell photoionization of oxygen - Gorczyca T.W.; Hasoglu M.F. (Institute of Physics Publishing, 2014)
R-matrix calculations of the 1s photoionization in oxygen are reported. Proper treatment of spectator Auger broadening, relaxation, pseudoresonace elimination, and shake-up/shake-off are addressed. © Published under licence by IOP Publishing Ltd.
Chinese Academy of Sciences;et al.;FEI;Institute of Physics Publishing Ltd;International Union of Pure and Applied Physics (IUPAP);National Natural Science Foundation of China
28th International Conference on Photonic, Electronic and Atomic Collisions, ICPEAC 2013 -- 24 July 2013 through 30 July 2013 -- Lanzhou -- 106035